The Influence of Internal Communication, Rewards and Punishment on Employee Work Motivation at PT. Galaxy Ocean Shipyard Tanjungpinang - Tiara; Siladja, Muljanto (Dinasti Publisher, 2025)
This research aims to determine the influence of internal communication, rewards and punishment on work motivation of PT employees. Tanjungpinang galaxy shipyard. The population in this study was 50 respondents who were employees at PT. Galaxy Ocean Shipyard Tanjungpinang. The sampling method in this research was saturated sampling, samples taken from all employees at PT. Galaxy Ocean Shipyard Tanjungpinang as many as 50 people. The type of research used in this research is quantitative descriptive. The data collection techniques used were in the form of questionnaires and literature studies. The data analysis techniques used are validity test, classical assumption test, classical assumption test, linear multiple regression test, hypothesis test with the help of the SPSS 23 program. The results of this research show that internal communication, reward and punishment influence employee work motivation.